Structure and morphology of electrospun collagen blends. Issue 4 (1st August 2012) - Collins, George; Ophir, Zohar; Banerjee, Angana; Matarlo, Blair; Jaffe, Michael; Arinzeh, Treena L.; Wang, Sherry
Abstract : Electrospinning collagen with a synthetic polymer has been frequently investigated as a method of fabricating composite micro and nanofibers for tissue engineering applications. Using trifluoroacetic acid as a solvent for collagen and poly(L-lactic acid) (PLLA), electrospun fibers were well formed, and the filament surface was relatively smooth, with diameters averaging around 350 nm. Thermal analysis showed evidence of a PLLA phase with a well-developed enthalpy recovery peak along with a lower temperature for cold crystallization as compared to the unprocessed PLLA pellets. These results can be interpreted in terms of the non-equilibrium configuration of the solid state in the nanofilament as a consequence of the high elongational flow and rapid vitrification that occurs during electrospinning resulting in extended polymer chains for PLLA. In the solid state, this extended conformation allows PLLA to rapidly collapse to a more dense state. This conformation can also facilitate the formation of crystals with minimum segmental diffusion. Transmission electron microscope and solid extraction experiments suggest that phase separation has occurred, with an extended interphase, sheath-core morphology where PLLA forms the sheath, while collagen is in the core. This morphology can account for previous observations that collagen-polymer blends are not soluble in physiological fluids.